Investment Development Before and During the Covid-19 Pandemic and Impact on Regional Economy in West Java - Ninik Anisah (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2021)
The Covid-19 pandemic has reduced economic growth in West Java, including investment growth explained by the decline in economic growth in the Gross Fixed Capital Formation component. Moreover, the primary measure that illustrates the economic region shows how much monetary value is formed to Gross Regional Domestic Product. This study looks at the investment conditions of Foreign Direct Investment, Domestic Direct Investment, and Government Capital Expenditures before and during the Covid-19 pandemic and the effect of these investments on the Regional Economic. The multiple regression analysis methods use the data to cross-section with individual districts and cities in West Java Province and the three investment variables. The analysis results explain that the Covid-19 pandemic has reduced Foreign Direct Investment and Government Capital Expenditure, on the other hand, increased Domestic Direct Investment. This increase in Domestic Direct Investment is related to the new businesses that are strongly related to the handling of the Covid-19 pandemic. Domestic Direct Investment and Government Capital Expenditure are still being felt on the region's economy before and during the Covid-19 pandemic, but Foreign Direct Investment has decreased. Before the Covid-19 pandemic, the real impact of Foreign Direct Investment came from the first and second years after investment. In contrast, during the Covid-19 pandemic, the real impact came from three years after invested Foreign Direct Investment.